Ovaries absent links dLsd1 to HP1a for local H3K4 demethylation required for heterochromatic gene silencing - Yang, Fu (eLife, 2019)
Heterochromatin Protein 1 (HP1) is a conserved chromosomal protein in eukaryotic cells that has a major role in directing heterochromatin formation, a process that requires co-transcriptional gene silencing mediated by small RNAs and their associated argonaute proteins. Heterochromatin formation requires erasing the active epigenetic mark, such as H3K4me2, but the molecular link between HP1 and H3K4 demethylation remains unclear. In a fertility screen in female Drosophila, we identified ovaries absent (ova), which functions in the stem cell niche, downstream of Piwi, to support germline stem cell differentiation. Moreover, ova acts as a suppressor of position effect variegation, and is required for silencing telomeric transposons in the germline. Biochemically, Ova acts to link the H3K4 demethylase dLsd1 to HP1a for local histone modifications. Therefore, our study provides a molecular connection between HP1a and local H3K4 demethylation during HP1a-mediated gene silencing that is required for ovary development, transposon silencing, and heterochromatin formation. Editorial note: This article has been through an editorial process in which the authors decide how to respond to the issues raised during peer review. The Reviewing Editor's assessment is that all the issues have been addressed (see decision letter).